Unforeseen severity in a case of neonatal cow milk protein allergy: a case report - Imran , Alizeh; Lakdawala, Fatima Mustafa; Khan, Shahzaib (Journal of the Pakistan Medical Association, 2024)
Cow milk protein allergy (CMPA) is one of the most common childhood allergies that manifests with a range of digestive symptoms and skin reactions, which usually resolve with age. In this report, we present the case of a one-month-old male who presented with a rare and severe manifestation of neonatal CMPA. The neonate underwent numerous hospital admissions due to a presentation that closely mimicked symptoms of a metabolic disorder and sepsis. Our primary objective is to highlight the significance of systematically considering or excluding a CMPA diagnosis, irrespective of the severity of presentation. This proactive approach may potentially reduce future complications among the affected paediatric population, thereby preventing prolonged hospitalisation and the associated disease burden, as seen in this case. Keywords: Cow milk protein allergy, Metabolic acidosis, Amino-acid based infant formula, Neonatal food allergy, CMPA.